Mandapa (pillared hall) of the Adinatha Temple - Temples of India Project Team (Jio Institute, 2024)
This is the mandapa (pillared hall) of the Adinatha Temple, which has a quadrangle at the centre surrounded by rectangular archways on its northern and southern sides. To the west, the mandapa is connected to the garbhagriha (sanctum sanctorum) via an antarala (antechamber). The tripartite division of the arches is the same on all sides. The arches are supported by piers on the corners of the row. The base colour of the interiors of the mandapa is white, on which it has beautiful paintings done using multiple colours.